Successful treatment of endoxifen overdose: A case report - Dave, Nahid; Karia, Sagar (Indian Journal of Case Reports, 2025)
Endoxifen is a direct protein kinase C inhibitor available in India for the management of bipolar disorder since 2021. Clinical studies show that endoxifen is as effective as divalproex sodium and has a good tolerability profile. Clinical data related to overdosage of endoxifen has not yet been reported. We hereby report the case of a 37-year-old female presenting with suicidal ingestion of 56 mg of endoxifen, leading to mild mania. No changes were observed in vital signs, laboratory parameters, electrocardiogram, or ophthalmic examination. This case report suggests a good tolerability profile of endoxifen.